A FAUNAL STUDY ON PLANT BUGS (HEMIPTERA: HETEROPTERA: MIRIDAE) IN THE CENTRAL PART OF SOUTH KHORASAN PROVINCE, IRAN (Acta Entomologica Serbica, 2023)
This research was carried out in 2022 in the central part of South Khorasan province, Iran. Twenty-two species of plant bugs (Hemiptera: Miridae) belonging to 17 genera and 3 subfamilies, including Deraeocorinae (1 genus and 1 species), Mirinae (8 genera and 9 species) and Phylinae (8 genera and 12 species), were collected and identified from different host plants. In this report, three species including Ectagela sp., Megacoelum brevirostre and Adelphocoris ticinensis were reported from South Khorasan province for the first time. All specimens are preserved in the insect collection of the Natural History Museum of the University of Guilan.